Studi Pembelajaran IPA Berlandas Blended Learning Pada Masa Covid-19 - Eva Ayu Dwi Sartika; Misbahul Jannah; Juniar Afrida (Institut Agama Islam Negeri Padangsidimpuan, 2022)
The world experienced a shock, namely the Covid-19 virus which took many victims so that it almost paralyzed all activities in all sectors, from the economy, health, to education. Considering that an incident like this happened, the government decided to instruct the implementation of an online-based system that was simultaneously carried out by all educational institutions in Indonesia. This is no exception at MTsN 4 Banda Aceh which applies Blended Learning. This study aims to analyze blended learning-based science learning during the Covid-19 period at MTsN 4 Banda Aceh. This research is a qualitative research that does not use statistics but collects data, analyzes it, which is then interpreted. The focus in this research is the application of the blended learning model in science learning during the Covid-19 period at MTsN 4 Banda Aceh. Data collection techniques were carried out by means of interviews and documentation. The number of respondents in this study were 7 respondents consisting of 1 educator and 6 students in class IX. Based on data analysis, it is known that in the online or online system, students and educators use WhatsApp and Classroom applications as a medium of communication between educators and students. The information obtained during online learning is in the form of learning from YouTube, Google, and textbooks. Offline learning, the media used is in the form of video through infocus. The information obtained is from textbooks, teacher books and books related to learning. Face-to-face learning is carried out while complying with health protocols.